Current Situations of Human Resource Management for Private Higher Education Institutions - Manomaikul, Peempiphat; Polsaram, Pansak; Bovornsiri, Varaporn (Dusit Thani College Journal, 2020)
The Purpose of this research is to analysis current situations of human resource management of the private higher education institutions. The sample includes 90 the rector, vice-rector for administration, Human Resources Management Committee including Dean or Vice-dean for administration of Science and Technology, Health Sciences and Social Sciences and Humanities from the total number of 31 private higher education institutions. The research instruments include the content analysis form and questionnaire. Meanwhile, frequency, percentage, mean standard deviation. The research results can be summarized as follows: Most of the respondents in this study were male, aged 40-49, with the highest level of education of Master’s Degree, no academic position, working period of 10-14 years, under the large private university, In Bangkok and be a member with the faculty level and be under the Social Sciences and Humanities. The current status of human resource management in private higher education institutions is moderate level. Considering each aspect of the human resources management process, it is found that private higher education institutions has a high level of training and human resource development. Job involvement and organizational engagement is moderate, human resource planning, working evaluation, recruitment and selection and human resource maintenance or compensation management respectively